Step * 1 1 1 2 1 1 of Lemma Legendre-roots-sq


1. : ℤ
2. i:ℕ1 ⟶ {x:ℝ
                    (x ∈ (r(-1), r1))
                    ∧ (Legendre(n 1;x) r0)
                    ∧ (r0 < (r((-1)^(n i)) Legendre((n 1) 1;x)))} 
3. ∀i:ℕ2. ((z i) < (z (i 1)))
4. 2 ≤ n
5. : ℕn
6. : ℝ
7. (x ∈ (if i=0 then r(-1) else (z (i 1)), if i=n then r1 else (z i))) ∧ (Legendre(n;x) r0)
⊢ x ∈ {x:ℝ
       (x ∈ (if i=0 then r(-1) else (z (i 1)), if i=n then r1 else (z i)))
       ∧ (Legendre(n;x) r0)
       ∧ (r0 < (r((-1)^(n i)) Legendre(n 1;x)))} 
BY
(MemTypeCD THEN Auto) }

1
1. : ℤ
2. i:ℕ1 ⟶ {x:ℝ
                    (x ∈ (r(-1), r1))
                    ∧ (Legendre(n 1;x) r0)
                    ∧ (r0 < (r((-1)^(n i)) Legendre((n 1) 1;x)))} 
3. ∀i:ℕ2. ((z i) < (z (i 1)))
4. 2 ≤ n
5. : ℕn
6. : ℝ
7. x ∈ (if i=0 then r(-1) else (z (i 1)), if i=n then r1 else (z i))
8. Legendre(n;x) r0
9. x ∈ (if i=0 then r(-1) else (z (i 1)), if i=n then r1 else (z i))
10. Legendre(n;x) r0
⊢ r0 < (r((-1)^(n i)) Legendre(n 1;x))


Latex:


Latex:

1.  n  :  \mBbbZ{}
2.  z  :  i:\mBbbN{}n  -  1  {}\mrightarrow{}  \{x:\mBbbR{}| 
                                        (x  \mmember{}  (r(-1),  r1))
                                        \mwedge{}  (Legendre(n  -  1;x)  =  r0)
                                        \mwedge{}  (r0  <  (r((-1)\^{}(n  -  1  -  i))  *  Legendre((n  -  1)  +  1;x)))\} 
3.  \mforall{}i:\mBbbN{}n  -  2.  ((z  i)  <  (z  (i  +  1)))
4.  2  \mleq{}  n
5.  i  :  \mBbbN{}n
6.  x  :  \mBbbR{}
7.  (x  \mmember{}  (if  i=0  then  r(-1)  else  (z  (i  -  1)),  if  i=n  -  1  then  r1  else  (z  i)))  \mwedge{}  (Legendre(n;x)  =  r0)
\mvdash{}  x  \mmember{}  \{x:\mBbbR{}| 
              (x  \mmember{}  (if  i=0  then  r(-1)  else  (z  (i  -  1)),  if  i=n  -  1  then  r1  else  (z  i)))
              \mwedge{}  (Legendre(n;x)  =  r0)
              \mwedge{}  (r0  <  (r((-1)\^{}(n  -  i))  *  Legendre(n  +  1;x)))\} 


By


Latex:
(MemTypeCD  THEN  Auto)




Home Index